DASAR PERTIMBANGAN HAKIM DALAM PENETAPAN PERKARA ISBAT NIKAH - Armalina, Armalina; Hidayah, Ardiana (Solusi, 2020)
Marriage isbat is a method by husband and wife who have been legally married according to religious law in obtaining state recognition of the marriage so that it is legally binding. Judges in carrying out their duties and authorities, especially judges under the environment of the religious court, are guided by the principles of Islamic personality in the Judicial Power Act, namely the religious court is one of the executors of judicial power for people seeking justice in Islam regarding certain cases. Courts in the religious court environment examine, decide and settle certain cases, one of which includes marital matters. Judge's considerations in setting a case specifically on marriage isbat, the judge must be guided by the Qur'an and the hadith of the Prophet, as well as ijtihad scholars on the values ​​of the philosophy of marriage law in the teachings of Islam. Marriage isbat provides legal certainty and usefulness. The existence of the determination of the case has its benefits and provides legal certainty on the legality of marriage both in religious law and in state law so that the legal objectives are achieved.